A Rare Case of Survival after Complete Traumatic Cricotracheal Separation. (21st June 2012) - Singh, Gautam Bir; Kummar, Rajiv; Verma, Neha; Rai, Anil K.
Abstract : We report the survival of an extremely rare case of complete cricotracheal transection following incisional trauma with knife. The clinical record underlines the importance of prompt airway management and immediate neck exploration in such cases. To the authors knowledge, such a case has not been reported previously in the literature.